Antenatal clinic and Stop Smoking Services staff views on "Opt-Out" referrals for smoking cessation in pregnancy: a framework analysis - Campbell, Katarzyna; Bowker, Katharine; Naughton, Felix; Sloan, Melanie; Cooper, Sue; Coleman, Tim (MDPI, 2016)
Introduction: UK guidance recommends routine exhaled carbon monoxide (CO) screening for pregnant women and “opt-out” referrals to stop smoking services (SSS) of those with CO ≥ 4 ppm. We explored staff views on this referral pathway when implemented in one UK hospital Trust. Methods: Seventeen semi-structured interviews with staff involved in the implementation of the new referral pathway: six antenatal clinic staff (before and after implementation); five SSS staff (after). Data were analyzed using framework analysis. Results: Two themes were identified: (1) views on implementation of the pathway and (2) impact of the pathway on the women. Generally, staff felt that following training, referrals were less arduous to implement and better received than expected. The majority believed this pathway helped engage women motivated to quit and offered a unique chance to impart smoking cessation knowledge to hard-to-reach women, who might not otherwise contact SSS. An unexpected issue arose during implementation—dealing with non-smokers with high CO readings. Conclusions: According to staff, the “opt-out” referral pathway is an acceptable addition to routine antenatal care. It can help engage hard-to-reach women and educate them about the dangers of smoking in pregnancy. Incorporating advice on dealing with non-smokers with high CO into routine staff training could help future implementations.